PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Najmul Laili; Nining Ika Wahyuni; Muhammad Miqdad (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
The fundamental goal of this research is to investigate the impact of various, debt, and company size play a role in the adoption of earnings management techniques. Companies in the banking sector that were traded on the Indonesia Stock Exchange (IDX) were the primary focus of the study, both in terms of the population and the sample. During the sampling phase, the researchers used a purposive sample strategy. The sample consisted of a total of 32 businesses. Descriptive statistics, tests of classical assumptions, multiple linear regression, analysis of coefficient of determination, F-test, and t-test were all used to compile this report. As can be seen from the data, the profitability variable does not play a significant role in the process of earnings management. Earnings management appears to be influenced by both the leverage variable and the firm's size.